Using null models to compare bacterial and microeukaryotic metacommunity assembly under shifting environmental conditions - Vass, Máté (Sci Rep, 2020)
Temporal variations in microbial metacommunity structure and assembly processes in response to shifts in environmental conditions are poorly understood. Hence, we conducted a temporal field study by sampling rock pools in four-day intervals during a 5-week period that included strong changes in environmental conditions due to intensive rain. We characterized bacterial and microeukaryote communities by 16S and 18S rRNA gene sequencing, respectively. Using a suite of null model approaches (elements of metacommunity structure, Raup-Crick beta-diversity and quantitative process estimates) to assess dynamics in community assembly, we found that strong changes in environmental conditions induced small but significant temporal changes in assembly processes and triggered different responses in bacterial and microeukaryotic metacommunities, promoting distinct selection processes. Incidence-based approaches showed that the assemblies of both communities were mainly governed by stochastic processes. In contrast, abundance-based methods indicated the dominance of historical contingency and unmeasured factors in the case of bacteria and microeukaryotes, respectively. We distinguished these processes from dispersal-related processes using additional tests. Regardless of the applied null model, our study highlights that community assembly processes are not static, and the relative importance of different assembly processes can vary under different conditions and between different microbial groups.